Experimental conditions to suppress edge localised modes by magnetic perturbations in the ASDEX Upgrade tokamak. (17th July 2018) - Suttrop, W.; Kirk, A.; Bobkov, V.; Cavedon, M.; Dunne, M.; McDermott, R.M.; Meyer, H.; Nazikian, R.; Paz-Soldan, C.; Ryan, D.A.; Viezzer, E.; Willensdorfer, M.
Abstract: Access conditions for full suppression of edge localised modes (ELMs) by magnetic perturbations (MP) in low density high confinement mode (H-mode) plasmas are studied in the ASDEX Upgrade tokamak. The main empirical requirements for full ELM suppression in our experiments are: 1. The poloidal spectrum of the MP must be aligned for best plasma response from weakly stable kink-modes, which amplify the perturbation, 2. The plasma edge density must be below a critical value, m −3 . The edge collisionality is in the range (ions) and (electrons). However, our data does not show that the edge collisionality is the critical parameter that governs access to ELM suppression. 3. The pedestal pressure must be kept sufficiently low to avoid destabilisation of small ELMs. This requirement implies a systematic reduction of pedestal pressure of typically 30% compared to unmitigated ELMy H-mode in otherwise similar plasmas. 4. The edge safety factor q 95 lies within a certain window. Within the range probed so far, , one such window, has been identified. Within the range of plasma rotation encountered so far, no apparent threshold of plasma rotation for ELM suppression is found. This includes cases with large cross field electron flow in the entire pedestal region.